Efficacy of Phage- and Bacteriocin-Based Therapies in Combatting Nosocomial MRSA Infections - Walsh, Lauren; Johnson, Crystal N.; Hill, Colin; Ross, R. Paul (Frontiers in Molecular Biosciences, 2021)
Staphylococcus aureus is a pathogen commonly found in nosocomial environments where infections can easily spread - especially given the reduced immune response of patients and large overlap between personnel in charge of their care. Although antibiotics are available to treat nosocomial infections, the increased occurrence of antibiotic resistance has rendered many treatments ineffective. Such is the case for methicillin resistant S. aureus (MRSA), which has continued to be a threat to public health since its emergence. For this reason, alternative treatment technologies utilizing antimicrobials such as bacteriocins, bacteriophages (phage) and phage endolysins are being developed. These antimicrobials provide an advantage over antibiotics in that many have a narrow-spectrum activity, enabling treatments to be selected based on the target (pathogenic) bacterium thus avoiding collateral damage to the microbiome. Bacterial resistance to these treatments occurs less frequently than with antibiotics, particularly in circumstances where combinatory antimicrobial therapies are used. Phage therapy has been well established in Eastern Europe as an effective treatment against bacterial infections. While there are no Randomised Clinical Trials (RCTs) to our knowledge examining phage treatment of S. aureus infections that have completed all trial phases, there are numerous clinical trials underway as well as several commercial phage preparations which are currently available to treat S. aureus. Bacteriocins have primarily been used in food and agricultural industries for bio-preservation applications. However, the idea of repurposing bacteriocins for human health is an attractive one considering their efficacy against many bacterial pathogens. Such obstacles are less of an issue for topical/local administration, for example application to the surface of the skin. Bacteriocins have also shown impressive synergistic effects when used in conjunction with other antimicrobials, including antibiotics, which may allow antibiotic-based therapies to be used more sparingly with less resistance development. This review provides an updated account of known bacteriocins, phages and phage endolysins which have demonstrated an impressive ability to kill S. aureus strains. In particular, examples of antimicrobials with the ability to target MRSA strains and their subsequent use in a clinical setting are outlined.